Outstanding Religious Figures of the Southern Region (Xix-xx Centuries) - Guliev, Samid (Scholarya Demo Journal of Ruby, 2019)
Since the advent of Islam, prominent scholars of Azerbaijan contributed to the development of Islamic sciences with their exceptional services. As stated in historical sources, scholars announced their fatwa (law, legal opinion) to Muslims from Baku, Nakhchivan, Ardabil, Lenkaran, Ganja, Yerevan and dozens of other cities. Although separate books contain information about these scholars, substantial researches about them have not been carried out. The graves of many religious figures from Azerbaijan are currently located in the city of Najaf (Iraq), Qum and Mashhad (Iran). Unfortunately, the names of such great scholars are not mentioned in the books. As a result of the establishment of the Soviet government and dominant policy in Azerbaijan, many religious figures fled from their homeland, changed their names to avoid exile, and some were secretly killed at the request of the communist government. The southern zone, in turn, has always contributed to the development of clergy and spiritual environment in Azerbaijan. Living with true Islamic values, our religious figures passed them on to people, taught secular science in educational centers apart from Islamic sciences, wrote scientific works, mobilized the population to fight the enemy when necessary and fought on the front lines themselves. People from all regions of the country rendered their services in the development of science and culture. Studying the religious history of the southern region, it becomes clear that the inhabitants of this region have made a greater contribution to our religious culture. Therefore, the article discusses spiritual people and religious figures who lived in the southern region in the 19th and 20th centuries. During the study, archival documents, manuscript sources and people’s memoirs have been used.